(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study investigates the impact of Content and Language Integrated Learning (CLIL) on vocabulary acquisition among young learners aged 6 to 12. CLIL, which integrates subject content teaching with foreign language instruction, has gained popularity as an effective approach to enhance bilingual competence. The research compares vocabulary development in learners exposed to CLIL with those receiving traditional language instruction. Data collected through vocabulary tests and classroom observations indicate that CLIL significantly improves the acquisition and retention of subject-specific vocabulary, while also supporting incidental learning of general language. Findings suggest that meaningful content engagement in CLIL facilitates deeper processing of new words, contributing to better long-term vocabulary retention. The study highlights the importance of combining CLIL methodologies with explicit vocabulary support to optimize language learning outcomes for young learners.